2005
DOI: 10.1088/0953-8984/17/35/r01
|View full text |Cite
|
Sign up to set email alerts
|

Vortex chains in anisotropic superconductors

Abstract: High-cT superconductors in small magnetic fields directed away from the crystal symmetry axes have been found to exhibit inhomogeneous chains of flux lines (vortices), in contrast to the usual regular triangular flux-line lattice. We review the experimental observations of these chains, and summarize the theoretical background that explains their appearance. We treat separately two classes of chains: those that appear in superconductors with moderate anisotropy due to an attractive part of the interaction betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 68 publications
(146 reference statements)
5
35
0
3
Order By: Relevance
“…37 Outside the superconductor, the resulting field inhomogeneity leads to a depth independent broadening, since z ≪ d, consistent with our results (inset of Fig. 3).…”
supporting
confidence: 90%
“…37 Outside the superconductor, the resulting field inhomogeneity leads to a depth independent broadening, since z ≪ d, consistent with our results (inset of Fig. 3).…”
supporting
confidence: 90%
“…Such decoration of the JVs by the PVs was clearly observed in experiment (see for example [4] and [14]). The interaction between pancakes and in-plane field in the form of JVs is known to produce zigzag deformation of PV stacks (see Fig.…”
Section: Interaction Potential Of Zigzag Vorticesmentioning
confidence: 56%
“…In particular, it has been noted that in certain directions it is possible to have the long-range attraction between the tilted vortex lines [2,3]. In bulk anisotropic superconductors this phenomenon is known to result in the formation of vortex chains in the regime of low magnetic fields (see [4] for a review). Indeed, the attraction between two vortices leads to the formation of a vortex pair.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the above theoretical concepts, in particular, the formation of vortex chains in tilted fields and the attraction of pancake stacks to Josephson strings, were nicely confirmed by experiments. Extensive reviews of vortex behavior in layered high--Tc superconductors can be found in [5,25,26]. However, despite extensive experimental efforts, a larger part of the theoretically predicted vortex configurations in anisotropic superconductors still remains to be confirmed.…”
mentioning
confidence: 99%